Nahdlatul Ulama's (NU) Perspective on LGBT: Between Moderation and Rejection - Sulaeman, Otong; Yulianti, Dina (Universitas Djuanda, 2025)
While previous studies on Nahdlatul Ulama (NU) often focus on its theological orientation or political engagement, little attention has been given to how its rejection of Lesbian, Gay, Bisexual, and Transgender (LGBT) practices is reconciled with its identity as a moderate Islamic organization. This study addresses that gap by examining how NU constructs and practices moderation while firmly opposing LGBT behavior. Using a qualitative approach through analysis of official documents and in-depth interviews with Muslimat NU figures, the study finds that NU’s rejection of LGBT is grounded in theological arguments from the Qur’an and Hadith, reinforced by socio-cultural considerations and the organizational principles of moderation. This rejection is institutionalized through fatwas and official statements—most notably the 2016 NU fatwa—which prohibit same-sex relationships, yet explicitly denounce discrimination and violence against LGBT individuals. Moderation is operationalized through educational, rehabilitative, and dialogical strategies rather than purely punitive measures, reflecting the organization’s selective adaptation to modern challenges within the “Islam Nusantara” framework. This dual commitment—upholding theological steadfastness while fostering inclusive social engagement—illustrates a dynamic form of Islamic moderation. The findings not only contribute to scholarly debates on reconciling moral conservatism with moderation in Islamic contexts but also provide actionable insights for policymakers and religious leaders in managing sensitive moral issues in pluralistic societies.